2021
DOI: 10.1016/j.clay.2020.105922
|View full text |Cite
|
Sign up to set email alerts
|

Reliability study under thermal and photonic stresses of sulforhodamine B (SRB) confined in layered double hydroxide (LDH)

Abstract: When sulforhodamine B (SRB) is entrapped in a tightly packed hybrid material composed of dodecylsulfate anions interleaved in layered double hydroxide, the organic dye is considered as a possible red-emitting phosphor for white light-emitting diodes (WLEDs). To confirm such promising potential, a reliability study is here undertaken and the materials and their associated silicone films are subjected to different thermal and photonic stresses. Optical properties, photoluminescence quantum yields and emission sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 27 publications
(31 reference statements)
0
10
0
Order By: Relevance
“…The strong dehydration of the former causes the loss of stacking and therefore indirectly the aggregation of the phosphors once they are no longer confined. 55 More investigation is required to improve phosphor hybrid assembly stabilization in this higher temperature domain above 100 1C. The emission spectra recorded after 3000 min (80 1C) and 7000 min (120 1C) of illumination by the blue LED illustrate this rapid drop in emission intensity for higher temperatures (Fig.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The strong dehydration of the former causes the loss of stacking and therefore indirectly the aggregation of the phosphors once they are no longer confined. 55 More investigation is required to improve phosphor hybrid assembly stabilization in this higher temperature domain above 100 1C. The emission spectra recorded after 3000 min (80 1C) and 7000 min (120 1C) of illumination by the blue LED illustrate this rapid drop in emission intensity for higher temperatures (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…The strong dehydration of the former causes the loss of stacking and therefore indirectly the aggregation of the phosphors once they are no longer confined. 55…”
Section: Resultsmentioning
confidence: 99%
“…16 Absolute PLQY of the Si-LDH40 film before and after the heat treatments Depending on the excitation wavelength, a greater or lesser loss of yield is observed after heat treatment. Legentil et al demonstrated that the pristine silicone film does not degrade at these temperatures [59], thus any loss in PLQY should be attributed to the LDH powder. Under 360 nm, a relative loss of approximately 3% and 5% only is observed after treatment at 85°C and 120°C respectively.…”
Section: Thermal Stability Of the Silicone Filmsmentioning
confidence: 99%
“…This phenomenon, called the pillaring effect, has been extensively studied using terephthalate (TA) as an interleaved anion for various applications [39,[54][55][56][57][58]. Legentil et al were the only ones to try to use this anion as a spacer to host SRB molecules between LDH layers, but it led to unsatisfactory results in terms of the resulting optical properties [59].…”
Section: Introductionmentioning
confidence: 99%
“…At 30min, the TOC of the membrane dropped from 10.48mg•L -1 to 4.74 mg•L -1 , the mineralization rate reached 54.76%. Combined with spectrum scanning, it was speculated that the azo bond and naphthalene ring of AO7 were oxidized to form aromatic compounds with benzene ring as the main body, some intermediate products can be further degraded into small molecule organics, finally mineralized into CO2 and H2O (Legentil et al 2021). According to previous research, tertiary butanol (TBA), methanol (MeOH), phenol, furfuryl alcohol (FFA), p-benzoquinone (p-BQ) and other substances are usually used to quench the freedom that may be generated in the catalytic degradation process.…”
Section: Identification Of Main Mechanisms In Co Ni Ldhs/pms System Degradation and Mineralization Of Orange ⅱmentioning
confidence: 99%